Gambaran Tingkat Pengetahuan Ibu Hamil Tentang Kehamilan Risiko Tinggi Di Bidan Praktik Mandiri Sutartik, SST Kabupaten Pamekasan Tahun 2016 - Nova Purmahardini (Akademi Kebidanan Aifa Husada Madura, 2019)
High-risk pregnancy is a number of situations and conditions and a general condition during pregnancy, childbirth, childbirth will pose a threat to the mental health of both the mother and the fetus. The purpose of this study is to describe the level of knowledge of pregnant women about high-risk pregnancies. The design of this study used a descriptive method, the population of this study were 35 pregnant women. The sampling method used is non probability, the total sampling type is a large sample of 35 respondents. Data collection uses the questionnaire method. The conclusion in this study is the level of knowledge of pregnant women about high-risk pregnancies, this is influenced by factors of age, education, and employment.